Authentic Assessment Management in Islamic Religious Education Learning under the Merdeka Curriculum in Junior High Schools - Salsabila Mustopa; Tarsono Tarsono (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2026)
This study aims to analyze the concept of assessment in the Merdeka Curriculum and to describe its implementation in Islamic Religious Education (PAI) learning at formal educational institutions in Indonesia. The method employed is a literature review by critically examining relevant scientific sources published between 2022 and 2026. The findings reveal that the Merdeka Curriculum introduces a fundamental paradigm shift in educational assessment through three primary instruments namely diagnostic assessment, formative assessment, and summative assessment, which are holistic, continuous, and oriented toward comprehensive student competency development. In the context of PAI learning, this approach proves considerably more capable of capturing students' character development, spirituality, and internalization of Islamic values authentically compared to conventional systems that focused almost exclusively on the cognitive dimension. The study further reveals that implementation still faces real obstacles including limited teacher competence, high administrative burden, cultural resistance to change, and inadequate infrastructure in various regions. This study concludes that successful transformation of PAI assessment requires strong synergy among teachers, school management, and integrated educational policy at all levels in order to achieve meaningful and sustainable educational change.